Histology of Glandular Stomach in Sambar Deer (Rusa unicolor) - Rajani, C.V.; Surjith, K.P.; Patki, H.S.; Patki, H.S.; Prakruthi, B.V.; Patgiri, S.; Indu V.R.; Maya, S. (Indian Journal of Veterinary Anatomy, 2024)
Sambar deer is a large, massive deer and categorized under the suborder Ruminantia. They are herbivores and possess a four chambered stomach. Histomorphological studies on the glandular stomach of sambar deer were conducted using specimens collected from three adult animals of either sex. Representative tissue samples of the abomasum were processed for routine paraffin embedding procedures; sectioned, stained and histological features were recorded. The abomasum revealed the four typical tunics: mucosa, submucosa, muscularis and serosa. Simple columnar epithelium lined the mucosa; epithelium extended into the lamina propria as gastric pits which further continued as branched glandular acini up to the muscularis mucosae. The acinar cells exhibited features of mucous secretory cells in the cardiac and pyloric zones. The mucosa of the large fundic zone presented numerous chief and parietal cells in addition the mucous cells. The gastric pits had maximum depth in the pyloric glandular zone. The glands were more tortuous and branched in the pyloric region whereas; in the fundic zone they were more or less straight. Tunica muscularis was composed of thick inner circular and thin outer longitudinal muscle layers. The serosa enclosed adipose tissue and nerve fibres.